Development of vegan bars with incorporation of heterotrophic Chlorella vulgaris. Structure, bioactivity and sensorial properties - Vala, Carolina Bastos (2021)
Mestrado em Engenharia Alimentar / Instituto Superior de Agronomia. Universidade de Lisboa